Hotspot temperature analysis of distribution transformer under unbalanced harmonic loads using finite element method - Mohd Wazir, Muhammad Haziq; Mat Said, Dalila; Mohd Yassin, Zaris Izzati; Abd Wahid, Siti Aisyah (International Journal of Electrical and Computer Engineering (IJECE), 2024)
In an electrical power distribution system, harmonic distortion is the most prominent power quality problem that causes long-term adverse effects such as failure of distribution transformers. Considering that most transformer problems are caused by heat losses due to the presence of harmonics, it was decided to use a numerical method with the highest accuracy, finite element method (FEM) to analyze the hot spot temperature (HST) of the thermal distribution transformer model. Through the use of COMSOL Multiphysics software, three phases of unbalanced harmonic loads are considered, which contribute to three different total harmonic distortion current (THDI) levels and five different insulation temperature classes. Using the IEEE C57.110-2018 guidance, the simulation outputs are then verified with HST results from the HST mathematical model. The findings indicated that with the increased loadings, the unbalanced harmonic currents have impacted the HST increment and distinguished the HST values between the phases.